2022
DOI: 10.1186/s13287-022-02984-z
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ enhances the efficacy of mesenchymal stromal cell-derived exosomes via miR-21 in myocardial infarction rats

Abstract: Background Mesenchymal stromal cells (MSCs) activated with IFN-γ elicit stronger physical effects. Exosomes (Exos) secreted from MSCs show protective effects against myocardial injury. This study aimed to determine whether Exos derived from IFN-γ-treated MSCs exhibit more potent cardioprotective function and the underlying mechanisms. Methods H9c2 cells or human umbilical vein endothelial cells (HUVECs) were treated with Exos isolated from MSCs (Ct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…DOX causes myocardial injury, to which OS and pyroptosis were closely linked 30,31 . Recent research revealed that MSC‐derived Exos protect against myocardial infarction and myocardial ischemia–reperfusion injury, so increasing attention is paid to their potential therapeutic values in treating myocardial problems 32,33 . To probe the specific role of BMSC‐Exos in DOX cardiotoxicity, this study was conducted to ascertain the function of BMSC‐Exos in OS and pyroptosis during DOX‐induced myocardial injury and the related mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…DOX causes myocardial injury, to which OS and pyroptosis were closely linked 30,31 . Recent research revealed that MSC‐derived Exos protect against myocardial infarction and myocardial ischemia–reperfusion injury, so increasing attention is paid to their potential therapeutic values in treating myocardial problems 32,33 . To probe the specific role of BMSC‐Exos in DOX cardiotoxicity, this study was conducted to ascertain the function of BMSC‐Exos in OS and pyroptosis during DOX‐induced myocardial injury and the related mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that exposing MSCs to interferon-gamma (IFN-γ) improved their therapeutic effect. The improved cardiac outcome, cardiomyocyte survival, reduced fibrotic scarring, and increased angiogenesis were associated with exosomes carrying miR-21a [79]. In hepatocytes, miR-21a has been shown to play a role in lipid metabolism [80].…”
Section: Myocardial Infarction and Strokesmentioning
confidence: 99%
“…Zhang et al obtained IFN-γ-loaded MSC-EVs by coculturing IFN-γ with MSCs. Then, IFN-γ-loaded MSC-EVs were used to treat a mouse MI model in the infarction region, increasing the amount of miRNA-21 and causing decreased fibrosis, reduced apoptosis of cardiomyocytes, and improved cardiac function [152].…”
Section: Loading Specific Molecules Into Evsmentioning
confidence: 99%